Prevention of Staphylococcus aureus lysis. - Bhaduri, S (1983)
Staphylococcus aureus S-6 cells grown in chemically defined media often lysed after exponential growth. Lysis could be prevented by the addition of alanine or proline before the culture reached stationary phase.